Modelling bank performance: a network DEA approach - Fukuyama, Hirofumi; Matousek, Roman (Elsevier, 2017)
In this paper, we develop a bank network revenue function to evaluate banks’ network revenue performance. The bank network revenue function, which extends the environmental revenue function and the two-stage network cost function, is constructed as the difference between total revenue and the reserves for possible loan losses to incorporate the roles played by non-performing loans in bank production. The second part of the paper then applies Nerlove's revenue inefficiency model. We consider revenue maximization in two stages. We apply this function to Japanese banks operating from September 2000 to March 2013.